2012
DOI: 10.1105/tpc.112.102921
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of an Indole-3-Acetic Acid Amido Synthetase from Grapevine Involved in Auxin Homeostasis

Abstract: Auxins are important for plant growth and development, including the control of fruit ripening. Conjugation to amino acids by indole-3-acetic acid (IAA)-amido synthetases is an important part of auxin homeostasis. The structure of the auxinconjugating Gretchen Hagen3-1 (GH3-1) enzyme from grapevine (Vitis vinifera), in complex with an inhibitor (adenosine-59-[2-(1H-indol-3-yl)ethyl]phosphate), is presented. Comparison with a previously published benzoate-conjugating enzyme from Arabidopsis thaliana indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
74
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 57 publications
9
74
0
Order By: Relevance
“…2B). The architecture of the AMP binding site is nearly identical to those described for previously reported GH3 protein structures (9,13,14). Sequence comparison of AtGH3.5 with the IAA-conjugating AtGH3.1, AtGH3.2, AtGH3.17, and VvGH3.1, the JA-Ile biosynthesis enzyme AtGH3.11, and the benzoate-conjugating AtGH3.12 emphasizes the similarity of this site across GH3 proteins that recognize diverse acyl acid substrates (Fig.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…2B). The architecture of the AMP binding site is nearly identical to those described for previously reported GH3 protein structures (9,13,14). Sequence comparison of AtGH3.5 with the IAA-conjugating AtGH3.1, AtGH3.2, AtGH3.17, and VvGH3.1, the JA-Ile biosynthesis enzyme AtGH3.11, and the benzoate-conjugating AtGH3.12 emphasizes the similarity of this site across GH3 proteins that recognize diverse acyl acid substrates (Fig.…”
Section: Resultsmentioning
confidence: 53%
“…This orientation would be a catalytically nonproductive binding orientation and likely results from charge repulsion between the negatively charged carboxylate of IAA and the phosphate of AMP. Peat et al (13) reported the structure of VvGH3.1 in complex with an inhibitor (adenosine-5′-[2-(1H-indol-3-yl)ethyl]phosphate; AIEP) that mimics the IAA reaction intermediate. An overlay of VvGH3.1 and AtGH3.5 highlights the similarity in IAA binding ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They show the protein complex in an unanticipated conformation leading to reorganization of the substrate-binding site, which may aid the nucleophilic attack during catalysis. To substantiate this theory, we superposed the FIN219 structure with open-form AtGH3.12 and closed-form VvGH3.1 (PDB ID code 4B2G) from grapevine (Vitis vinifera) (39). An ATP analog, α,β-methylene adenosine 5′-triphosphate (AMPCPP) in the AtGH3.12 structure, shows a similar binding position to the inhibitor adenosine-5′-[2-(1H-indol-3-yl)ethyl]phosphate (AIEP) in the VvGH3.1 structure.…”
Section: Resultsmentioning
confidence: 99%
“…Although mutants of AtGH3.12/PBS3 display SA-related phenotypes in Arabidopsis, SA is not a substrate of this protein, and the physiologically relevant substrate is not known (94). The grapevine protein (VvGH3.1) conjugates IAA with aspartate (96). These structures define the overall GH3 fold as a large N-terminal domain with a ␤-barrel and two ␤-sheets flanked by ␣-helices and a smaller C-terminal domain consisting of a single four-stranded ␤-sheet flanked by two ␣-helices on each side (Fig.…”
Section: Plant Hormone-amino Acid Conjugationmentioning
confidence: 99%
“…Across the structures, the nucleotide site is identical to residues conserved in not only GH3 proteins but also the ANL superfamily (83,95,96). Three motifs define this site.…”
Section: Plant Hormone-amino Acid Conjugationmentioning
confidence: 99%